Uma concepção do ensino de matemática em tempo de pandemia - Rodrigues, Aronildo Pereira (Universidade Federal do Tocantins, 2023)
The Covid-19 pandemic has changed people's behavior. In this sense, schools adopted a new teaching model, called remote teaching. With the confirmation of the first case of Covid-19 in Brazil, school classes were suspended in March 2020, as a way to prevent the spread of the virus. In this sense, the remote/hybrid teaching modality was adopted. Before the pandemic, the use of technology tools was not common, with this, teachers and students found it difficult to teach in this new modality, there was a need to verify the difficulties faced by teachers and students. The objective of this research was to collect information about the challenges and difficulties faced by teachers and students in remote/hybrid teaching for the teaching of mathematics at Escola de Boa Vista de Belém. The study methodology attributed to the questionnaire application method was adopted. The results indicate that the printed material and the WhatsApp application were the resources most made available by teachers, and the main difficulties encountered were how to evaluate the activities passed on and identify students' doubts remotely. The questionnaire answered by the students indicated that most students do not have access to the internet and have difficulties in understanding the content without the physical presence of the teacher.